Microwave-Assisted Metathetic Synthesis and Characterization of Fe3O4 Incorporated BaMoO4:Er3+/Yb3+ Composites - Sung Lim, Chang (Asian Journal of Chemistry, 2013)
Fe3O4 incorperated Er3+/Yb3+ co-doped BaMoO4 (BaMoO4:Er3+/Yb3+) composites were successfully synthesized by a cyclic microwave-assisted metathetic route. The microstructure exhibited a well-defined and homogeneous morphology with sizes of 1-2 μm for the BaMoO4:Er3+/Yb3+ particles and 0.1-0.5 μm for the Fe3O4 particles, respectively. The Fe3O4 particles were self-preferentially crystallized and immobilized on the surface of BaMoO4:Er3+/Yb3+ particles. The synthesized Fe3O4 incorporated BaMoO4:Er3+/Yb3+ composites were characterized by X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Optical properties were examined by using photoluminescence emission data and Raman spectroscopy.